(3EUdGM GdNdd GdhGbY aj cJGH GdLeds - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s; (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe,J (B377 (3g`s ((3YeQ Hf Nda s)
(3ChdgG (B:s
(3bGd GdTjN CHh eMeO YHO Gddg GdMeO ddg GdPi de jJNP hdjkG hdG XgjQkG , hNdb cd TF abOQg JbOjQkG s
(3BNQgG (B:s
(3ef HGH GdJUQja , bhdg (B: (3hbO LYd CHh GdbGSe GdeYJd HGdUMjM ef VQhQI GdTYQ ai eG JbOe , hLYdg gGgfG dZI ceG JQi , hGddg CYde Je cJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HBNQgG Jedjcs
(3bdjd GdfbWs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdfMhs